(untitled) (Baghdad Science Journal, 2018)
It was aimed to understand the interleukin-4 (IL-4) role in etio-pathogenesis of rheumatoid arthritis (RA). Two approaches were adopted. In the first one, a quantitative expression of IL4 gene was assessed by reverse transcription-quantitative polymerase chain reaction (RT-qPCR), and such findings were correlated with some demographic, clinical and laboratory parameters, which included gender, duration of disease, disease activity score (DAS-28), rheumatoid factors (RFs), C-reactive protein (CRP) and anti-cyclic citrullinated peptide (ACCP) antibodies. In the second approach, a single nucleotide polymorphism (SNP) of IL4 gene (rs2243250) was inspected by DNA sequencing using specific primers. Fifty-one Iraqi RA patients (22 males and 29 females) were enrolled in the study. They were under therapy, which was a single weekly subcutaneous dose of 25 mg of etanercept (Enbrel) for a period of 3-5 years. The results of gene expression (2-??Ct) revealed an increased expression of IL4 mRNA (Mean ± SEM: 8.247 ± 2.442), especially female patients compared to male patients (11.545 ± 3.928 vs. 3.537 ± 1.530; p = 0.03). The expression was also subjected to variations that were related to clinical and laboratory findings. With respect to IL4 gene SNP, allele and genotype frequencies showed no significant differences between RA patients and controls. In addition, the SNP genotypes had no effect on IL4 gene expression. In conclusion, an up-regulation of IL4 gene expression was observed in RA patients, and it was more pronounced in female than male patients by approximately four folds, while no association between the IL4 SNP alleles or genotypes and RA was observed.